2016
DOI: 10.1007/s00431-016-2778-7
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic tubulointerstitial nephritis on treatment with isotretinoin

Abstract: Isotretinoin is a vitamin A-derived agent which is commonly used in the treatment of acne and may cause drug-related acute tubulointerstitial nephritis. What is Known: •Drug-related acute tubulointerstitial nephritis (ATIN) is one of the most common causes of childhood acute renal failures. What is New: •Isotretinoin may cause drug-related acute tubulointerstitial nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…In this case report, a patient was diagnosed with acute tubulointerstitial nephritis. Pathological signs of renal biopsy sections had been revealed interstitial mononuclear cell and eosinophilic infiltration in this case (11). Armaly et al (10) had been reported a 17-year-old female who experienced acute kidney injury to using isotretinoin.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…In this case report, a patient was diagnosed with acute tubulointerstitial nephritis. Pathological signs of renal biopsy sections had been revealed interstitial mononuclear cell and eosinophilic infiltration in this case (11). Armaly et al (10) had been reported a 17-year-old female who experienced acute kidney injury to using isotretinoin.…”
Section: Discussionmentioning
confidence: 50%
“…There are conflicting reports about safety of oral isotretinoin on kidneys. Some authors reported that it may be toxic (9)(10)(11)(12)(13). Some authors suggested that it is safe on kidneys (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations